Indicações geográficas: a proteção do patrimônio cultural brasileiro na sua diversidade - Rocha Filho, Sylvio do Amaral (2009)
Geographic Indications (GI s) do not have uniform treatment in the world-wide doctrine what is reflected in the diverse manifestations about it as demonstration of itself, therefore in each place the institute is treated as peculiar and unique. Even in only one country GI s have, many times, different treatments. We understand Law ex facto oritur jus (from the fact law is born) and from that, we create our agreement of what it is happening in the domain of the Geographical Indications. Geographical indication is a set of words that aims to transmit only one concept, but in fact, it apparently transmits two disconnected concepts that are not: 1 - Geographical indication is the official nomination of one certain place where a Good of the same name occurs and is typical, regional and peculiar with guarantee of origin and with traditional and recognized quality for the loyal, responsible and constant repetition. 2 - Geographic indication is the typical, regional and peculiar Good, with a certain name officially recognized as originating of a place, region or country, named differently but granting quality, reputation and characteristic recognized for the loyal, responsible and constant repetition. Geographic indication is for the target of this work the sort from which flows out the two types: Indication of Source (IS) and Appellation of Origin (AO). It must be noticed that in the same region or place the two types can coexist, that is, a same place can present Indication of Source and Appellation of Origin, depending. An Indication of Source is a local manifestation of more generic character; an Appellation of Origin is a local manifestation of very typical character and, consequently, more generous. Beyond these trouble makers factors there are others: the doctrine does not deal with and does not even mention the several internal classifications of quality that permeate a Geographical Indication and tint it; it insists only on the mention to Geographical Indication, Indication of Source and Appellation of Origin as if it was enough, without informing that almost always there is a proper qualitative internal system of each Geographical Indication, system that enlarges, accentuates or diminishes the classic divisions into Geographical Indication and its species Indication of Source and Appellation of Origin with which it always coexists, case by case